ANALYSIS OF FACTORS INFLUENCING THE INCREASE CAPACITY FACILITIES SURABAYA MAINTENANCE AND REPAIR ON THE WARSHIPS REPUBLIC OF INDONESIA THE HEADQUARTERS COMMAND FLEET 2 - Joko Setiaji; Priyadi Hartoko; Ayip Rivai Prabowo (Indonesian Naval Technology College STTAL, 2021)
The ability to carry out the maintenance and repair of Warships of the Republic of Indonesia / naval vessels is a concept used in assessing the achievement of work with time parameters and measures of success. Budget, infrastructure and human resources have an important role in the task of maintenance and repair facilities surabaya. Every maintenance and repair always expects the implementation of the work to be completed on time, and the maximum results, so that the ability to maintain and repair needs to be maintained and improved on the implementation of the work. There are several alternative factors that can lead to improved maintenance and repair capabilities of warships of the Republic of Indonesia / Naval vessels including budget allocation, supporting infrastructure directly or indirectly as well as the readiness of human resources that include willingness, experience and expertise. These factors have an interconnected pattern. This study aims to find out the main factors that affect the improvement of the ability to maintain and repair KRI / KAL in mako koarmada II. In this study used a measuring instrument called dynamic system method with stella software. Factors that affect the improvement of capabilities in the literature can be from the literature whereas, the determination of the main factors that affect is done by modeling dynamic systems. This dynamic system modeling is done by creating a dynamic relationship between the factors that affect productivity. The data collection in this study uses secondary data from the process of maintenance and repair of fasharkan in Surabaya. The scale of the data used to determine the factors that influence the improvement of the ability is modeled in qualitative form. The result of modeling dynamic system factors that affect the improvement of capability is budget, infrastructure facilities and human resources factors that dominate are human resource factors. Keywords: Proficiency, Dynamic System, Stella Software